Pathogenesis of failure in the anastomosis integrity and a prophylactic program in surgical treatment of the colon diseases. - V. I. Rusyn; S. M. Chobey; O. O. Dutko (Клінічна хірургія)
Objective. To establish the impact of intraintestinal pressure on the intestinal anastomosis integrity and to propose a prophylactic measures of its insufficiency in surgical treatment of the colon diseases.